EP 57. Biological motion perception in Parkinson's disease. Issue 9 (September 2016) - Kloeters, S.; Hartmann, C.J.; Schnitzler, A.; Südmeyer, M.; Lange, J.
Abstract : Previous studies have suggested that action perception is linked to action execution. For example, it has been shown that perception of an action is altered by simultaneous performance of the same action (Jacons and Shiffrar, 2005 ). Parkinson's disease (PD) is typically characterized by impaired motor execution. In the present study, we investigated whether PD also adversely affects biological (i.e. human) motion perception. 17 PD patients and 17 matched neurologically healthy controls participated in the study. The participants watched point-light displays of human, animal and object motion and were asked to differentiate between biomechanically plausible point-light motions and distorted versions of these motions. All participants completed two identical testing sessions. The PD patients completed the first testing session in an "OFF"-state, that is 12 hours after last taking dopaminergic medication. The second testing session was completed after the ingestion of levodopa ("ON"). Control subjects completed two identical session with a break of ∼30–60 min in between. The Unified Parkinson's Disease Rating Score (UPDRS) was measured in OFF and ON for the PD group to ensure an effect of medication. We analyzed participants' sensitivity for plausible vs. distorted motion. In the OFF state, PD patients showed significantly lower sensitivity for human and animal motion than controls. Post hoc analysis revealed that the difference between PD patients and controls was significantly stronger for transitive than for intransitive human motions. Sensitivity for object motion did not differ between both groups. In the second testing session, controls showed a slight improvement of performance compared to the first session, probably due to learning effects. PD patients, however, showed no improvement of performance in the ON state (i.e., second session) compared to the OFF state. This might be due to adverse side-effects of the medication, e.g., fatigue. Our results confirm the hypothesis that PD patients who are impaired in motor execution are also impaired in the perception of human and animal motion. It has been argued that perception of actions and action execution interact in the human mirror neuron system. Mirror neurons are cells that respond to both the execution and observation of motion (Rizzolatti and Craighero, 2004 ). We propose that human and animal motion perception deficits in patients with Parkinson's disease might be caused by mirror neuron system dysfunction.